The acute effects of single football match on whole blood viscosity and hematological variables in female soccer players - Duzova, Halil; Karakoc, Y.; Gullu, E.; Gullu, A.; Koksal, B.; Esen, B. (Scientific Publishers India, 2016)
In this study, we aimed to investigate the acute effects of single 90-minute football match on whole blood viscosity and hematological variables in amateur female soccer players. Ten subjects were selected from the female footballers of an amateur regional football club in Turkey, at the last week of football season. Prior to last seasonal football match venous blood samples were drawn. After 90 minute football match, the researchers stopped the match timely and blood samples were redrawn from subjects. From the samples, pre- and post-match hematological parameters, lactate level, blood viscosity, plasma Na+ and K+ levels were determined. The results showed that mean corpuscular volume (MCV), Na+ and K+ levels were all decreased significantly whereas numbers of white blood cell (WBC) and platelet (PLT) were both increased after the match. We didn't find statistically significant difference in whole blood viscosity after the match. Blood lactate levels were also significantly increased after the match. Our results showed that blood viscosity of female footballers tends to increase by this type of training due to decrease in body waters and increase in WBC and PLT numbers of amateur female footballers. Increase in blood lactate levels is remarkable and may have adverse effect on blood viscosity of these subjects because some protective mechanisms might not have adequately developed with regular training throughout the season.
Keywords: Soccer; Female footballer; Hematological variables; Blood viscosity; Lactate level